2020
DOI: 10.1002/aur.2374
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Emotional Electrodermal Activity in Toddlers with Autism Spectrum Disorder

Abstract: Past studies in autism spectrum disorder (ASD) indicate atypical peripheral physiological arousal. However, the conditions under which these atypicalities arise and their link with behavioral emotional expressions and core ASD symptoms remain uncertain. Given the importance of physiological arousal in affective, learning, and cognitive processes, the current study examined changes in skin conductance level (ΔSCL) in 41 toddlers with ASD (mean age: 22.7 months, SD: 2.9) and 32 age‐matched toddlers with typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Puppets' physical appearance, voice, and playfulness can also serve as powerful sources of positive emotions. As shown in recent studies, despite otherwise atypical emotional reactivity profiles (Macari et al, 2018; Vernetti et al, 2020), toddlers with ASD displayed largely normative joyful emotional responses to puppets engaging in playful interactions on both behavioral and physiological levels (Macari et al, 2018; Vernetti et al, 2020). There is extensive evidence that positive emotions increase levels of dopamine in the brain, a neurotransmitter which plays a key role in motivation, reinforcement, and executive function, and facilitates learning, flexibility, and problem‐solving (Ashby & Isen, 1999; Shiota et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Puppets' physical appearance, voice, and playfulness can also serve as powerful sources of positive emotions. As shown in recent studies, despite otherwise atypical emotional reactivity profiles (Macari et al, 2018; Vernetti et al, 2020), toddlers with ASD displayed largely normative joyful emotional responses to puppets engaging in playful interactions on both behavioral and physiological levels (Macari et al, 2018; Vernetti et al, 2020). There is extensive evidence that positive emotions increase levels of dopamine in the brain, a neurotransmitter which plays a key role in motivation, reinforcement, and executive function, and facilitates learning, flexibility, and problem‐solving (Ashby & Isen, 1999; Shiota et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…There is a large body of literature describing autonomic dysregulation in autism. The profile in autism is typified by high basal sympathetic (fight or flight) tone, lower parasympathetic (rest and digest) activation, and low sympathetic reactivity to certain stimuli including tests of orthostatic tolerance [ 105 , 106 , 107 , 108 ]. However, a small percentage of more severely affected cases tend to have sympathetic under activation except when engaging in self-injurious behaviors, which suggests these behaviors are a form of autonomic self-regulation.…”
Section: Symptom Overlap Between Autism and Ehlers-danlos Syndromementioning
confidence: 99%
“…In one study, Macari and colleagues [Macari et al, 2018] employed the Laboratory Temperament Assessment Battery – Locomotor Version (Lab‐TAB) [Gagne, Van Hulle, Aksan, Essex, & Goldsmith, 2011; Goldsmith & Rothbart, 1999] and showed attenuated intensity of fear in response to nonsocial threat (approach by novel objects) compared to developmentally delayed (DD) and typical developing (TD) controls. Lower intensity of distress to nonsocial threat in toddlers with ASD was accompanied by significantly lower changes in physiological arousal measured by skin conductance levels compared to TD controls [Vernetti et al, 2020]. In contrast, Scherr and colleagues [Scherr, Hogan, Hatton, & Roberts, 2017] reported that in response to social threat (approach by a stranger), preschool children with ASD exhibited more intense facial expressions of fear compared to TD and Fragile X comparison groups.…”
Section: Introductionmentioning
confidence: 99%